Crustal Structure of Northwestern Iran on the Basis of Regional Seismic Tomography Data - Amir Talebi; Irina Medved; Ivan Koulakov (Geosciences, 2025)
This study presents a 3D seismic velocity model of the crust beneath northwestern Iran. The data include arrival times of 76,589 P-waves and 10,796 S-waves from 7245 events recorded by 233 stations. The seismic velocity model presented in this research provides a detailed understanding of the crustal structure and tectonic processes shaping northwestern Iran. The interplay between volcanism, fault activity and mantle dynamics has produced a complex velocity structure. The findings in the region offer new insights into the geodynamic evolution of this tectonically active area. Understanding these features is crucial for assessing the region’s seismic hazard and geothermal potential, particularly in light of its active tectonic faults and volcanic systems. Moreover, the crust of northwestern Iran represents a two-layered structure: a high P-velocity upper crust and low-velocity lower crust. The authors documented a similar structure on the basis of tomographic data of different collision regions, such as Eastern Anatolia, Tien Shan and Pamir–Hindu Kush. The structure concerned is supposed to be due to delamination processes in the upper mantle.